Hydroxylamino‐Anchored Poly(Ionic Liquid)s for CO2 Fixation into Cyclic Carbonates at Mild Conditions. (12th November 2020) - Zhang, Jinwei; Li, Xiaopeng; Zhu, Zheng; Chang, Tao; Fu, Xiying; Hao, Yongjing; Meng, Xiaocai; Panchal, Balaji; Qin, Shenjun
Abstract: Catalytic utilization of CO2 addition into chemicals has potential as a strategy for removing CO2 from the atmosphere. In this context the additive‐free catalytic conversion of CO2 into cyclic carbonates in the absence of metal and solvents under mild conditions is a major challenge. Herein, a series of hydroxylamino‐tethered polymeric ionic liquids bearing adjustable alkyl length substitutes are constructed from copolymerization of divinyl benzene and vicinal hydroxyl and amino base monomeric ionic liquids synthesized from 1‐glycidyl‐3‐vinylimidazolium bromide with alkyl amine. The polymeric ionic liquids are used in CO2 ‐epoxide cycloaddition reactions to prepare cyclic carbonates and demonstrate high efficiency and stable reusability without a co‐catalyst under atmospheric pressure and under solvent‐free conditions. The introduction of alkyl groups on an ionic polymer host backbone can accelerate the reaction process. A preliminary kinetic study is performed using [PDVB‐HAVIM‐C18 ]Br and the activation energy is calculated as 53.2 kJ mol −1 . A hydrogen bonding and Br – ion synergistic catalytic mechanism is proposed to account for the excellent catalytic activity of the synthesized ionic polymer. Abstract : A series of hydroxylamino‐anchored polymeric ionic liquids are fabricated and applied to a CO2 fixation reaction with epoxides under mild conditions. The synergistic interaction of hydrogen bonding and Br – ions plays an important role in the reaction. A preliminary kinetic study is performed using [PDVB‐HAVIM‐C18 ]Br and the activation energy is calculated as 53.2 kJ mol −1 .